Pragmatic Memory - Mark Mack (Oz, 1990)
I am an architect who removed himself from the Old World and positioned himself in the New World where history is taking a faster and condensed form and creating a constant challenge to architectural concepts. When the challenge is met, architecture carries the memory of that segment of history.